2022
DOI: 10.1007/s11912-022-01228-w
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Tyrosine Kinase Inhibitors in Patients with Chronic Myeloid Leukemia: a Review of the Biological Factors Associated with Treatment-Free Remission

Abstract: Purpose of Review Clinical factors alone do not enable us to differentiate which patients will maintain treatment-free remission (TFR) from those who are likely to relapse. Thus, patient-specific factors must also play a role. This review will update the reader on the most recent studies presenting biological factors that can help predict tyrosine kinase inhibitor (TKI) discontinuation success. Recent Findings Cellular and molecular factors with a suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…1 However, ongoing lifelong treatment with TKIs can significantly reduce quality of life, lead to offtarget effects, such as life-threatening cardiovascular TherapeuTic advances in hematology or liver toxicity, and represent a significant financial burden. 2,3 Therefore, successful treatmentfree remission (TFR) has become a new therapeutic goal, and large, prospective data has shown encouraging results. In the Stop Imatinib (STIM) study, molecular recurrence-free survival (RFS) at 60 months was 38% [95% confidence interval (CI): 29-47%] with no disease progression among patients in whom BCR::ABL1 transcripts were not detected for >2 years.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, ongoing lifelong treatment with TKIs can significantly reduce quality of life, lead to offtarget effects, such as life-threatening cardiovascular TherapeuTic advances in hematology or liver toxicity, and represent a significant financial burden. 2,3 Therefore, successful treatmentfree remission (TFR) has become a new therapeutic goal, and large, prospective data has shown encouraging results. In the Stop Imatinib (STIM) study, molecular recurrence-free survival (RFS) at 60 months was 38% [95% confidence interval (CI): 29-47%] with no disease progression among patients in whom BCR::ABL1 transcripts were not detected for >2 years.…”
Section: Introductionmentioning
confidence: 99%
“…51,136,137 Other possible markers include regulatory T cells, cytotoxic CD8+ T lymphocyte (CTL), and somatic mutations. 134,[138][139][140] Type of BCR-ABL1 transcript also has a role; in a study by D'Adda et al, TFR maintenance was observed to be higher in CML patients with e14a2 transcript when compared with e13a2 transcripts. 141 However, all of these biomarkers are not readily available for routine clinical use, and thus, clinical parameters remain the most widely used or accessible parameters for TFR.…”
Section: Predictors and Biomarkers For Tfrmentioning
confidence: 99%
“…These hallmarks may be useful as prognostic biomarkers of longer TFR [ 67 ]. Further clinical trials are needed to test these predicting biomarkers for TFR [ 69 ]. Moreover, the memory-like NK cells, characterized as CD3 − CD56 dim CD57 + NKG2A − NKG2C + , were increased in patients with TFR success [ 70 ].…”
Section: Dasatinib-mediated Immunomodulatory Effects In CMLmentioning
confidence: 99%